Yanbu'a Method: A Solution to Increase Students' Proficiency in Al-Qur'an Education - Arjoni, Arjoni; Oktavia, Gifa; Akmal, Fauzi; Zeky, Serpuadi; Fajri, Julnal; Febriani, Afifah (Al-Hashif: Jurnal Pendidikan dan Pendidikan Islam, 2024)
Religious education, especially in learning the Qur'an, has a significant role in the spiritual and moral development of the younger generation. However, many students in various educational institutions, including the Qur'anic education center, face difficulty reading, writing, and memorizing the Qur'an properly. This study aims to determine and analyze the effectiveness of the Yanbu'a method in the aspects of reading, writing, and memorizing the Qur'an in students. This study uses a qualitative method with a descriptive approach, involving interviews, observations, and documentation studies for data collection. The results of the analysis show that the application of the Yanbu'a method has succeeded in significantly improving the ability of students to read, write, and memorize the Qur'an. Repetition and imitation are key in the learning process. However, there are obstacles to the mastery of the method by teachers and the writing ability of students in lower classes. The results of the study indicate the need for training for teachers in the Yanbu'a method to improve the effectiveness of teaching the Qur'an in similar educational institutions.